Morphological digital filtering. - Yañez Suarez, Oscar (Revista Mexicana de Ingenieria Biomedica, 1991)
Morphological filters are non-linear transformations that are carried out on n-dimensional signals to locally modify their geometric characteristics. The theoretical foundations of these transformations definitively move away from the usual lines of digital signal processing such as convolution or Fourier transformation; and may, in the first instance, be disconcerting. The language of morphological filtering is that of set theory and its theoretical root is the mathematical morphology, algebra of sets introduced by Matheron (1) and Serra (2) in the early eighties.